2018
DOI: 10.1159/000485378
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Mean Corpuscular Volume for Detection of Advanced Colorectal Cancer in Patients Older than 85 Years

Abstract: Background/Aims: The aim of this study was to elucidate clinical indicators for the detection of advanced colorectal cancer (ACRC). Methods: This was a retrospective study conducted at a tertiary hospital. This study included 333 patients older than 85 years who underwent colonoscopy from April 2006 to May 2010. The detection rate of ACRC was assessed. Then, we analyzed the association between the detection of ACRC and various background factors including mean corpuscular volume (MCV). We also analyzed the cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…MCHC is calculated according to MCH and MCV results (MCHC=MCH/MCV), and showed the optimal sensitivity and specificity with CRC prognostic risk, so we selected MCHC to be included in our ARR formula. Kato et al reported that [52] , MCV was an independent predictor irrespective of the location of the tumor, whereas anemia symptom was not an independent predictor. Other studies suggest otherwise [46] , lower MCV was associated with advanced T stage and proximal tumor location, while HGB in patients with tumors in proximal colon was significantly lower relative to distal colon and rectum.…”
Section: Discussionmentioning
confidence: 97%
“…MCHC is calculated according to MCH and MCV results (MCHC=MCH/MCV), and showed the optimal sensitivity and specificity with CRC prognostic risk, so we selected MCHC to be included in our ARR formula. Kato et al reported that [52] , MCV was an independent predictor irrespective of the location of the tumor, whereas anemia symptom was not an independent predictor. Other studies suggest otherwise [46] , lower MCV was associated with advanced T stage and proximal tumor location, while HGB in patients with tumors in proximal colon was significantly lower relative to distal colon and rectum.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, there were several studies focusing on the clinical role of MCV in CRC, showing MCV was associated with the risk of colorectal adenoma ( 10 ), advanced CRC ( 11 ) and response to chemotherapy in CRC ( 12 , 13 ) with even conflicting results and only one study was available investigating the prognostic role of pretreatment MCV in CRC patients ( 16 ). In this study, Hidemasa and his colleagues carried out a retrospective analysis in 1174 patients with stage I, II, and III CRC, and it was found that MCV of <80 fL was a favorable prognostic factor in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…As a measure of the average volume of a red blood cell, mean corpuscular volume (MCV) was related to the prognosis of liver cancer ( 7 ), esophageal cancer ( 8 ) and adenocarcinomas of the gastroesophageal junction ( 9 ). Interestingly enough, MCV was also reported to be associated with the risk of colorectal adenoma ( 10 ), advanced CRC ( 11 ) and response to chemotherapy in CRC ( 12 , 13 ), suggesting MCV had the potential to be an ideal biomarker and be put into clinical application. In particular, previous study revealed that high MCV value may be used as an index of the risk of colorectal adenomas ( 10 ), but a recent research reported decreased MCV was an independent predictor for the detection of advanced colorectal cancer ( 11 ), indicating that the clinical role of MCV in colorectal cancer was still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Kato M [25] suggested that the decrease of MCV could be used as an independent predictor of late CRC and further colonoscopy was necessary for people over 85 years with the decrease of MCV. In our study, the MCV of NAFLD-CRC (88.59 ± 9.27 fl) and nonNAFLD-CRC (88.29 ± 8.37 fl) is significantly lower than that of NAFLD-NonCRC (90.89 ± 6.78 fl, P < 0.001).…”
Section: Correlation Between Gender Age and Crc In Nafld Populationmentioning
confidence: 99%